Analisis Fraud Pentagon Mendeteksi Potensi Financial Statement Fraud Perusahaan IDX30 Bursa Efek Indonesia - Rachmawati, Susan; Martias, Andi; Sudirja, Sudirja; Wahyuhening F, Firstianty (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to determine the possibility of financial statement fraud by using Pentagon fraud analysis. Pentagon fraud is a concept that explains the factors that cause someone to commit fraud, namely pressure, opportunity, rationalization, ability, and management. In this research, stress factors are proxied through the use of financial goals and external stress. Opportunity factors are proxied by utilizing industry characteristics and effective monitoring. The rationalization factor is proxied using Changes in Auditors. The competency factor is represented by changes in management use. Finally, proxy the arrogance factor using the number of frequent Key Management images. This study uses the F-score model to see the possibility of false financial reports. The sample for this research is 30 IDX30 companies listed on the Indonesia Stock Exchange from 2020 to 2024 that meet certain criteria. The analysis technique used is panel data regression analysis and hypothesis testing using the t-test. The results of this research indicate that the variables financial objectives and management changes are proven to have a significant positive effect on the likelihood of detecting financial statement fraud, however the nature of external pressures and industry variables have a negative impact on the likelihood of detecting financial report fraud. Meanwhile, effective monitoring variables; Replacing auditors and management has no impact on the detection of financial reports that have the potential to be fraudulent.